Yes, We Can (No, You Can't): Weight Stigma, Exercise Self-Efficacy, and Active Fat Identity Development. Issue 2 (4th May 2019) - Meadows, Angela; Bombak, Andrea E.
ABSTRACT: An inverse relationship has been observed between body mass index and physical activity levels. In the present article, we draw from a range of literatures to construct a novel, theoretical dual-pathway model that identifies direct and indirect impacts of societal weight stigma on exercise behavior. The direct pathway operates via experiences or threat of stigma and discrimination, which create traumatic learning experiences and impair the development of exercise self-efficacy. The indirect pathway impedes engagement in physical activity due to the absence of positive representations of fat exercisers, and a glut of negative representations, resulting from societal anti-fat attitudes. Thus, fat people lack role models from whom they may develop vicarious self-efficacy. Low self-efficacy, in turn, hinders the development of active fat identities. We review the existing literature for evidence supporting such a model, identify directions for future research, and briefly consider the implications of this framework for public health and policy aims.